Sequencing the CHO DXB11 genome reveals regional variations in genomic stability and haploidy - Kaas, Christian Schrøder (BMC Genomics, 2015)
BACKGROUND: The DHFR negative CHO DXB11 cell line (also known as DUX-B11 and DUKX) was historically the first CHO cell line to be used for large scale production of heterologous proteins and is still used for production of a number of complex proteins. RESULTS: Here we present the genomic sequence of the CHO DXB11 genome sequenced to a depth of 33x. Overall a significant genomic drift was seen favoring GC → AT point mutations in line with the chemical mutagenesis strategy used for generation of the cell line. The sequencing depth for each gene in the genome revealed distinct peaks at sequencing depths of 0x, 16x, 33x and 49x coverage corresponding to a copy number in the genome of 0, 1, 2 and 3 copies. This indicate that 17% of the genes are haploid revealing a large number of genes which can be knocked out with relative ease. This tendency of haploidy was furthermore shown to be present in eight additional analyzed CHO genomes (15-20% haploidy) but not in the genome of the Chinese hamster. The dhfr gene is confirmed to be haploid in CHO DXB11; transcriptionally active and the remaining allele contains a G410C point mutation causing a Thr137Arg missense mutation. We find ~2.5 million single nucleotide polymorphisms (SNP’s), 44 gene deletions in the CHO DXB11 genome and 9357 SNP's, which interfere with the coding regions of 3458 genes. Copy number variations for nine CHO genomes were mapped to the chromosomes of the Chinese hamster showing unique signatures for each chromosome. The data indicate that chromosome one and four appear to be more stable over the course of the CHO evolution compared to the other chromosomes thus might presenting the most attractive landing platforms for knock-ins of heterologous genes. CONCLUSIONS: Our studies reveal an unexpected degree of haploidy in CHO DXB11 and CHO cells in general and highlight the chromosomal changes that have occurred among the CHO cell lines sequenced to date. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1391-x) contains supplementary material, which is available to authorized users.